Division on the Christian right: Republican pastors and the use of force - Shady, Stephanie N. (Politics and religion, 2024)
Polarization in American politics has not produced unity among conservative Christians. Drawing from original survey and interview data on Republican pastors in North Carolina, this paper seeks to understand why these pastors are divided on the legitimacy of force defending the "traditional American way of life." We find (1) that theological fundamentalism has a positive, though weak, influence; (2) Christian nationalism and White grievance are powerful in increasing support for the use of force; and (3) distrust of elections intensifies the effect of these attitudes.